Analisis Karakteristik Kepemimpinan Perempuan terhadap Perannya dalam Pendidikan Kejuruan - Cahyaningsih Cahyaningsih (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
A relatively unanalyzed issue of women's leadership is women's leadership in vocational education. The purpose of this study is to determine the characteristics of women's leadership in vocational education, as well as the influence of women's leadership characteristics on the role of women's leadership in vocational education. This study uses a mixed methods research method. This study uses a mixed methods mixed model, which is a research procedure in which researchers combine quantitative and qualitative data to obtain a comprehensive analysis to answer the research problem. In the quantitative stage, researchers conducted research on the leadership characteristics of 90 female principals in vocational education and followed by in-depth interviews with female principals. The qualitative data analysis process was carried out in five stages, namely: Compiling, Disassembling, Reassembling, Interpreting, Concluding. The findings of this study are strategies to improve the role of women's leadership in education which include: characteristics of women's leadership in vocational education are motherly, thrifty, meticulous, careful, responsive and tolerant, adaptable, creative and innovative, open communication. Women's leadership characteristics have a positive influence on the role of women's leadership in vocational education.